2014
DOI: 10.1016/j.seizure.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of levetiracetam drug levels to assist with seizure control and monitoring of drug interactions with other anti-epileptic medications (AEMs)

Abstract: LEV range (20-40mg/L) assisted epilepsy management and anti-epileptic medication interactions were suggested with polytherapy thus possibly explaining the impaired efficacy of LEV with polytherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
51
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 22 publications
2
51
2
Order By: Relevance
“…[8][9][10][11]14,15 In the current study, ngLEV was also well tolerated. Less than 10% of the total analyzed patients had mild LEVrelated side-effects (slight rash and somnolence).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…[8][9][10][11]14,15 In the current study, ngLEV was also well tolerated. Less than 10% of the total analyzed patients had mild LEVrelated side-effects (slight rash and somnolence).…”
Section: Discussionmentioning
confidence: 50%
“…15 The DZP-resistant group had a higher blood LEV level than the DZP-responders. One plausible reason for the significant difference between two groups was that the DZP-resistant group included a greater number of ngLEV 3000 mg patients ( Table 2).…”
Section: Discussionmentioning
confidence: 91%
“…It was shown that patients may reach optimal seizure control with AED plasma levels often below reference ranges. [44][45][46] Individual reference ranges (referring to drug levels associated with a response in an individual patient) might also be more useful in clinical practice, 10,39,[47][48][49] but assessing this aspect went beyond our aims.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report suggests that high doses may still be possible without toxicity. 1 Purpose To describe the importance of therapeutic drug monitoring (TDM) of LEV for minimising toxicity when it is used at doses higher than recommended. Material and methods Casereportof57-years-oldmalediagnosedwith symptomaticfocalepilepsyandhumanimmunodeficiencyvirus(HIV).…”
mentioning
confidence: 99%